A Suspected Pelvic Aneurysmal Bone Cyst in Pregnancy. (16th April 2013) - Elkattah, Rayan; Foulk, Brooke
Abstract : Albeit rare, the majority of identified bone lesions in pregnancy spare the pelvis. Once encountered with a pelvic bone lesion in pregnancy, the obstetrician may face a challenging situation as it is difficult to determine and predict the effects that labor and parturition impart on the pelvic bones. Bone changes and pelvic bone fractures have been well documented during childbirth. The data regarding clinical outcomes and management of pregnancies complicated by pelvic ABCs is scant. Highly suspected to represent an aneurysmal bone cyst, the clinical evaluation of a pelvic lesion in the ilium of a pregnant individual is presented, and modes of delivery in such a scenario are discussed.